Estrogen deficiency accelerates lumbar facet joints arthritis - Hao Chen (Nature Portfolio, 2017)
Abstract Dramatic increase in the prevalence of lumbar facet joint (LFJ) arthritis in women around the age of menopause indicates a protective role for estrogen in LFJ arthritis. To date, there is no evidence for this indication and the mechanism of such an effect remains poorly understood. In this study, ovariectomized (OVX) mice were used to mimic the estrogen-deficient status of post-menopausal women. Micro-CT and immunohistochemistry was employed to assess the morphological and molecular changes in ovariectomy-induced LFJ arthritis. The results show that the LFJ subchondral bone mass was significantly decreased in OVX mice, with increased cavities on the interface of the subchondral bone. Severe cartilage degradation was observed in ovariectomy-induced LFJ arthritis. Increased blood vessels and innervations were also found in degenerated LFJ, particularly in the subchondral bone area. 17β-Estradiol treatment efficiently suppressed LFJ subchondral bone turnover, markedly inhibited cartilage degradation, and increased blood vessel and nerve ending growth in degenerated LFJ in OVX mice. Our study reveals that estrogen is a key factor in regulating LFJ metabolism. Severe LFJ degeneration occurs when estrogen is absent in vivo. Collapsed subchondral bone may be the initiation of this process, and estrogen replacement therapy can effectively prevent degeneration of LFJ under estrogen-deficient conditions.